On the Road to Maracas Bay; Over Mountains, Trinidad, B.W.I. - (:unkn) unknown (Ace Studio, Trinidad, 2009)
The picture show a newly cut mountain road that leads to Maracas Bay on Trinidad's North Coast. The road was built by United States armed forces during World War II as a United States naval base at Chaguaramas prohibited the sea going public entry to Chaguaramas and the then popular bathing beaches of Staubles Bay and Tetron Bay. The ruling British government had leased Chaguaramas to them for supplementary security during this war period by the agreement of the 2nd September 1940, concerning naval and air bases. Postcard number 13.
Colour: Black and White; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Beaches--Trinidad and Tobago; Mountain roads--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; United States--Armed Forces; Maracas Bay